A study on malaria cases in hilly areas and Terai belt of Nepal - Singh, KRN; Sah, Ram Bilakshan; Pokharel, PK (Health Renaissance, 2017)
Introduction: Malaria is a well-known disease and it continues to be a major public health problem at the start of new millennium. The problem is persistent not only amongst the city dwellers but also amongst the rural population. Objective: To identify the magnitude of malaria cases and to compare the malaria cases between hilly area and Terai belts. Methods: This cross-sectional study was carried out in Terai belt of Morang District Nepal at Nobel Medical College & Research Center Biratnagar from March to Oct 2007 and hilly area around Lumbini Medical College Teaching Hospital & Research Center Pravas, Tansen, Palpa of Nepal between March to December 2008. Blood samples were collected from all the cases and malaria parasites were examined by Peripheral Blood Smear Examination and Rapid Card Method Screening. Results: Thirty-five cases were malaria positive from hilly area of whom 80% had Plasmodium vivax infection. Whereas in Terai belt 231 positive cases ware recorded. Out of them (62.8%) cases were affected by Plasmodium vivax infection. That most vulnerable age group was 15 years and above. Males were more affected than females. Conclusion: It was observed that in hilly areas the numbers of positive cases are less than the Terai belt. The magnitude of malaria cases are found high in July. A steady decline has been observed till September to October Health Renaissance 2015;13 (1): 4-12